DYNAMICS OF FERMENTATION PROCESS OF BREAD DOUGH PREPARED WITH DIFFERENT TYPES OF YEAST - GABRIELA-MARIANA MUNTEANU; GHEORGHE VOICU; MARIANA FERDEȘ; ELENA-MĂDĂLINA ȘTEFAN; GABRIEL-ALEXANDRU CONSTANTIN; PAULA TUDOR (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The dough fermentation process is a major step for obtaining good quality bread because the yeast cells, which release CO2, have a major influence on dough rheology, volume, texture and taste of final bread product. The fermentation speed of the dough is strongly influenced by the fermentative performance of the yeast and dough fermentation conditions. Therefore, this paper presents the dynamics of the yeast fermentation process prepared with three commercial types of dry yeast, namely: Pakmaya, Dr. Oetker, Rapunzel. It has been experimentally found that besides the dynamics of the fermentation process, there are also changes in the physico-chemical properties of the dough, but also of the bread obtained from the three types of dough.